Distributed control of positive systems - Rantzer, A. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
Stabilization and optimal control is studied for state space systems with nonnegative coefficients (positive systems). In particular, we show that a stabilizing distributed feedback controller, when it exists, can be computed using linear programming. The same methods are also used to minimize the closed loop input-output gain. An example devoted to distributed control of a vehicle platoon is examined.